Optimization of Pectin Extraction from Albedo of Watermelon (Citrullus lanatus) using Response Surface Methodology - Pagarra, Halifah; Rachmawaty, Rachmawaty; Sahribulan, Sahribulan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This research delves into the utilization of albedo of watermelon rind as a potential source of pectin, a vital polysaccharide with wide-ranging applications in food and pharmaceutical industries due to its gelling and stabilizing properties. The study specifically focuses on the extraction of pectin from watermelon (albedo) using advanced methodologies like central composite design (CCD) and response surface methodology (RSM). These methods allow for the optimization of key processing parameters: temperature (at levels of 60, 80, and 100°C), pH (at levels of 1.5, 2.0, and 2.5), and extraction time (at levels of 60, 90, and 120 minutes). The study's findings highlight how these factors have a major impact on the amount of pectin that is extracted. The complex link between the input variables (temperature, pH, and extraction time) and the final pectin yield is thoroughly explained by means of a second-order polynomial model. Notably, the study identifies optimal conditions for pectin extraction, where the highest yield of 6.42% was achieved. These optimal conditions entail a temperature of 100°C, pH of 1.5, and extraction time of 60 minutes. Furthermore, the research highlights the individual impact of temperature, pH, and extraction time on pectin yield, demonstrating their significant roles in the extraction process. By providing insights into the optimization of pectin extraction from albedo of watermelon this study contributes to the broader understanding of utilizing agricultural by-products for value-added applications in various industries.